Survival Strategies of Riverbank Communities: A Structural and Cultural Analysis of Existence and Resistance in West Kalimantan - Annisa Dwi Lestari; Putri Rahmah Nur Hakim; Bibi Suprianto; Dahniar Musa; Asyifa Nadia Jasmine (Jurnal Community, 2026)
Riparian communities in West Kalimantan face a persistent dilemma between ecological risks and the need to sustain their living space. This study aims to analyze how riverbank communities construct their existence and resistance amid structural constraints, ecological pressures, and deeply rooted cultural ties. The research employs a qualitative approach, drawing on secondary data and social media discourse. Data were analyzed using content analysis and in-depth interpretive techniques to understand the social practices of riverbank communities. The findings reveal three main preconditions that drive communities to remain and resist relocation policies: (1) river ecology as a space for learning and adaptation; (2) structural constraints that limit mobility and alternative settlement options; and (3) the river as a source of collective identity encompassing memory, emotion, and meaning of life. These findings indicate that survival strategies are not solely based on rational-economic considerations but are also shaped by riparian habitus formed through historical and sociological processes. This study concludes that the existence and resistance of riverbank communities are produced through a dynamic interplay of ecological, structural, and cultural factors that cannot be separated. As a result, top-down relocation policies tend to be ineffective as they overlook the cultural dimensions and lived experiences of the communities. This study recommends the adoption of an emic and holistic approach in policymaking, emphasizing participatory engagement with communities and integrating social, cultural, and ecological dimensions in a comprehensive manner.